The tropical fowl mite Ornithonyssus bursa (Acari: Mesostigmata: Macronyssidae) parasitizing the European starling Sturnus vulgaris (Aves: Passeriformes: Sturnidae), an invasive bird in central Argentina: an approach to the bacterial fauna of this mite - Lareschi, Marcela (2017)
The tropical fowl mite (Ornithonyssus bursa) is a common parasite of domestic and wild birds in tropical and subtropical regions. This mite can cause irritation, severe dermatitis and anemia. The European starling (Sturnus vulgaris) is an invasive bird in Argentina. Both O. bursa and S. vulgaris have high reproductive rates with implications for public health. The goals of our study were to report the occurrence of this mite parasitizing the starlings, and test for the presence of bacteria that could be potentially associated with the mites. The study was conducted in Estación de Cría de Animales Silvestres (Buenos Aires, Argentina). Mites were collected from starlings and stored in 96% ethanol, and prepare for their identification under an optic microscope. Molecular studies were conducted in order to examine the presence of bacteria. All mites were identified as O. bursa. We detected for the first time Wolbachia sp., associated with the genus Ornithonyssus. In contrast, mites were negative for species of Rickettsia, Bartonella and Borrelia. In addition to the damage that the starlings produce as an invasive species in central Argentina, herein we report the association of these birds with O. bursa, favoring the dispersal of the mites and their colonization to other birds.